Association of annual volume and in‐hospital outcomes of catheter‐directed thrombolysis for pulmonary embolism. Issue 2 (27th January 2022) - Jung, Richard G.; Simard, Trevor; Hibbert, Benjamin; Harris, Alyssa H.; Hohmann, Samuel F.; Giri, Jay S.; Bashir, Riyaz; Alkhouli, Mohamad
Abstract: Objective: We sought to evaluate the association between the institutional volume of catheter‐directed thrombolysis (CDT) for pulmonary embolism and in‐hospital mortality. Background: CDT is an increasingly utilized therapy in patients with intermediate/high‐risk PE. However, data on the relationship between hospital volume and clinical outcomes remain limited. Methods: Patients who underwent CDT between October 1, 2015, and March 31, 2021, were identified in the Vizient Clinical Database. The primary outcome was in‐hospital mortality. Secondary outcome were major complications, length of stay, and cost. Hospitals were dichotomized into <8 and ≥ 8 cases/year following restricted cubic spline analysis. Results: A total of 6741 CDT procedures at 171 hospitals were included with a median annual hospital volume of 4.1 cases (IQR = 1.9–8.3). A total of 44 hospitals (25.7%) were classified as high‐volume ( ≥ 8 cases/year) and performed 60.9% of all CDT cases. CDT at high‐volume centers was associated with lower in‐hospital mortality (6.0% vs. 11.3%; p  < 0.0001). Stroke and bleeding rates were similar, but pulmonary complications were more frequent at low‐volume centers. CDT at high volume centers was associated with a significantly shorter length of stay and lower cost. The association between high CDT volume and in‐hospital mortality persisted after adjustment for demographics (odds ratio [OR] = 0.49, [0.41–0.58]), demographics and risk factors (OR = 0.52 [0.44–0.62]), and demographics, risk factors, and troponin elevation (OR = 0.51 [0.40–0.66]). Conclusion: In a large contemporary cohort of patients undergoing CDT in the United States, low annual institutional volume of CDT was associated with higher in‐hospital mortality.